Enhancing Customer Satisfaction Index for Electric Bus service in Aligarh smart city: A case study on critical attributes and improvement strategies - Khan, Rahman Ali; Humam, Mushfiq; Fazli, Mohammad Farhan (International Journal of Engineering and Technology, 2024)
Public transportation serves as a critical infrastructure in developing countries, essential for promoting mobility and sustainability. However, traditional transit systems often contribute to environmental degradation through emissions. Recognising this challenge, nations such as India are actively pursuing strategies to reduce energy consumption and carbon emissions. An important initiative involves integrating electric buses into urban transit systems. To optimise the effectiveness of these electric bus services and encourage greater public transportation usage, it is essential to align service offerings with customer needs and expectations. This research aims to assess customer satisfaction among electric bus users in Aligarh using the Customer Satisfaction Index (CSI) analysis. Critical attributes such as affordability, safety, comfort, and accessibility will be examined to identify areas for improvement. An analysis will be conducted to gain insights into service quality attributes crucial for enhancing customer satisfaction in public transportation operations and the strategies for improving customer satisfaction to be defined.